The study of crack resistance of TiAlN coatings under mechanical loading and thermal cycle testing; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Akulinkin A. Alexandr; Shugurov A. Artur; Panin A. V. Alexey Viktorovich; Sergeev V. Viktor; Cheng C.-H. (2015, 2015)
Title screen